Construction of oil palm (Elaeis guineensis Jacq.) genetic linkage map and mapping of yield-related quantitative trait loci - Mohd Shaha, Fakhrur Razi (2020)
Oil palm (Elaeis guineensis Jacq.) is one of the major oil-producing crops that provide great nutritional value and high economic returns. Genotyping-by-sequencing (GBS) provides a platform to accelerate the discovery of single nucleotide polymorphisms (SNP) and insertion and deletions (InDel) markers for the construction of a genetic linkage map. The genetic linkage map facilitates the identification of quantitative trait loci (QTL) associated with the trait of interest. Together these approaches will speed up the process in identifying markers for marker-assisted selection (MAS) in oil palm breeding programmes. A total of 112 full sibling mapping population from a cross of a Deli dura and a Serdang pisifera was used in this study. Reduced representation libraries (RRL) of 112 F1 progeny and the two parents were sequenced, and the reads were mapped against E. guineensis reference genome. A total of 2.5 million SNPs and 153,547 InDels were identified. However, only a subset of 5,278 markers comprising 4,838 SNPs and 440 InDels were informative for the construction of linkage map. The sixteen linkage groups spanned 2,737.6 cM for the maternal map and 4,571.6 cM for the paternal map with the average marker densities of one marker per 2.9 cM and 2.0 cM, respectively. Phenotypic data were correlated with polymorphic markers to discover markers flanking QTL regions for fresh-fruit-bunch yield (FFB), oil yield (OY), oil-to-bunch (O/B), oilto- dry mesocarp (O/DM), oil-to-wet mesocarp (O/WM), mesocarp-to-fruit (M/F), kernel-to-fruit (K/F), shell-to-fruit (S/F), and fruit-to-bunch (F/B) ratio. Two significant QTLs for M/F were detected with PVE value of 20.6% and 23.9%, four markers for K/F were detected with PVE value range from 19.4% to 25.6%, and a marker for S/F was successfully detected with PVE value of 18.1%. The QTL peaks detected for K/F, M/F and S/F were significant with the logarithm of odds (LOD) value ranging from 4.51 to 6.24, which surpassed the genome-wide LOD threshold. Meanwhile, the allele effect analysis showed alleles associated with these three traits could contribute to the trait improvement from 4.6% to 20.7%. These findings, including a dense linkage map and identification of significant QTL regions associated with K/F, M/F and S/F that could be applied in MAS in the oil palm breeding programme. In addition, these approaches using the oil palm genetic linkage map and QTL analysis could fast-track the process of generating new oil palm varieties as compared to the oil palm conventional breeding method.